Tinjauan Meta-Analisis Efektivitas Model Pembelajaran PBL dalam Meningkatkan Hasil Belajar Peserta Didik (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study examines the effectiveness of the Problem-Based Learning (PBL) model in improving elementary school students’ learning outcomes by reviewing 15 national journal articles published between 2018 and 2024. The results show that PBL significantly enhances students’ abilities in cognitive, affective, and psychomotor domains, with improvements ranging from 7.1% to 83.3%. PBL encourages students to think critically, participate more actively in learning, and develop problem-solving skills through real and relevant situations. However, its implementation still faces several challenges, such as limited teacher training, inadequate facilities, and difficulties in shifting from conventional methods to this new approach. Based on the analysis, three main factors determine the success of PBL: appropriate learning design, the teacher’s ability to guide the PBL process, and the availability of supporting learning resources. The most significant positive impacts are seen among fifth-grade students and in schools located in the Java region. In conclusion, PBL is highly effective when supported by proper teacher training and adaptation to field conditions. Therefore, further teacher development programs and additional research on the long-term effects of implementing this model are strongly recommended.